Second-order moment equations for a system of differential equations with random right-hand side - Valeyev, K. G.; Dzhalladova, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We present a method for the derivation of second-order moment equations for solutions of a system of nonlinear equations that depends on a finite-valued semi-Markov or Markov process. For systems of linear differential equations with random coefficients, the case where the inhomogeneous part contains white noise is considered.